ANALYSIS OF FACTORS INFLUENCING IN BRINGING OPERATING INDICATORS OF CENTRIFUGAL SEDIMENTATION PUMPS TO STABLE MODE - Abdirazakov Akmal Ibragimovich; Boyjonov Afzalshoh Fathiddin ogli (Scholar Express Journals, 2026)
This article presents the results of monitoring and analyzing the performance indicators of centrifugal submersible pumps used in oil wells when they are stopped under the action of well pressure, as well as when centrifugal submersible pumps are stopped due to technical and geological conditions, and the degree of influence of the flow direction device on the heating temperature of the pump, preventing overheating of the submersible electric motor of the pump.
Keywords: Oil; well; centrifugal pump; steady state